Influence of Pre-Harvest Spray on Seed Infestation and Seed Quality in Field Bean (Lablab purpureus L.) - ANAND; BASAVARAJA B; HARISH MS; VISHWANATH K (Seed Research, 2026)
A field experiment was conducted at ARS Madenur, Hassan to investigate the influence of preharvest spraying of insecticides and botanicals on pulse beetle and storability of seeds in field bean (Labalab purpureus L.) var. HA-4 sown during Rabi 2022. Foliar treatments of insecticides and botanicals were used as a pre-harvest sanitation spray at pod maturity stage. Threshed pods were dried to a safer moisture level. Freshly harvested seeds were collected after harvest and graded seeds were taken for initial observation in the laboratory. Among different pre-harvest sprays, Spinosad 45 SC @ 0.04 ml/l resulted in highest 100 seed weight (19.30 g), germination (91.25%), seedling vigour index-I (3728) and seedling vigour index-II (6862), higher total dehydrogenase activity (2.50), lower electrical conductivity of seed leachates (239.25 µScm-1), and nil seed infestation (0.00%), eggs laid (0.00), and eggs hatched (0.00. This study showed that in field bean spraying with Spinosad 45SC @0.04 ml/l at pod maturity stage can be practised as a sanitation measure for bruchid management.